Analysis of the "ADIARTA" Innovation as the Savior of Batu City Land Archives - Rabbani, Imdad; Lentera Sukma Mahardika; Fiona Niska Dinda Nadia (Jurnal Ilmiah Sumber Daya Manusia, 2024)
The ADIARTA innovation that was selected as the top 45 commendable public service innovations at the Public Service Innovation Competition (KIPP) was initiated by the Batu City Government, the Library and Archives Office, and the Communication and Information Office to facilitate services in the field of land archives. It is aimed at digitizing land documents to extend the life of the land archives of the Batu City community. In addition, ADIARTA is an application that can provide information about land ownership, buying and selling, grants, and the history of land in Batu City. ADIARTA is one of the innovations that can encourage community service and efforts to save village land archives which are confidential and sensitive documents (vital archives). The implementation of ADIARTA in Batu City has not been fully carried out in all villages, with the help of Malang State University students and the ADIARTA team. The realization of these innovations is to support good governance, effectiveness, and efficiency of public services to the community. From all kinds of problems about land, the Batu City government launched a land innovation that had a positive impact on the people of Batu city, as many as 90% of people felt satisfaction from ADIARTA services. The utilization of information and communication technology is one of the steps that can provide cost savings, time savings, and ease of access for related parties. The innovation is expected to be one way to provide efficiency to operations, facilitate community accessibility in accessing land archives, provide security and sustainable services, and improve public services for the community